1999
DOI: 10.1111/1467-7660.00130
|View full text |Cite
|
Sign up to set email alerts
|

Female Demographic Disadvantage in India 1981–1991: Sex Selective Abortions and Female Infanticide

Abstract: Using evidence from a number of sources (including the 1981 and 1991 censuses of India, prior research, and NGO reports), this article examines whether bias against girl children persists during periods of development and fertility decline, whether prenatal sex selection has spread in India as elsewhere in Asia, and whether female vs. male child mortality risks have changed. The authors present estimated period sex ratios at birth (SRBs) calculated by reverse survival methods along with reported sex ratios amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 25 publications
3
98
0
1
Order By: Relevance
“…As a result, women's literacy and educational attainment is much higher in southern India than in northern India, where no comparable educational reforms have taken place (Saradamoni 1994). Arguably, regional differences in inheritance, kinship system, and educational investment partially account for the disproportionately higher skewed sex ratios in northern and northwestern states of India compared to southern states (Sudha and Rajan 1999).…”
Section: Sociocultural and Economic Drivers Of Son Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, women's literacy and educational attainment is much higher in southern India than in northern India, where no comparable educational reforms have taken place (Saradamoni 1994). Arguably, regional differences in inheritance, kinship system, and educational investment partially account for the disproportionately higher skewed sex ratios in northern and northwestern states of India compared to southern states (Sudha and Rajan 1999).…”
Section: Sociocultural and Economic Drivers Of Son Preferencementioning
confidence: 99%
“…If employed women have fewer total children, and if boys are considered higher quality than girls, then this may contribute to sex ratios skewed towards boys. Women's employment may be associated with increases in son preference by providing lower status/lower caste women with the resources to emulate the preferences and cultural practices of higher status/higher caste families (Basu 1999;Sudha and Rajan 1999).…”
Section: Why Might Women's Paid Employment Be Associated With Changesmentioning
confidence: 99%
“…Sex differences in early life mortality exist in most of the developing world, with parts of South and East Asia showing particularly severe excess female infant and child mortality (Bandyopadhyay 2003;Croll 2000;Sudha and Rajan 1999). Population sex ratios strongly favoring males in these same regions also appear to provide evidence of son preference, as higher male child mortality in other societies eliminates the survival advantage males have at infancy, and results in sex ratios close to unity by young adulthood and even lower thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Available data reveals the use of prenatal sex determination techniques (PNDT), as the major cause of decreased female births. An article published in Lancet analysed Indian Census data and concluded that selective abortion of the female foetus has increased in India over the past few decades due to increased prenatal sex determination and has contributed to widening imbalance in the child sex ratio 5,6,7 . The abuse of advanced technologies coupled with social factors such as dowry and looking up to the son as a breadwinner has made the evil practice of female feticide.…”
Section: Introductionmentioning
confidence: 99%